THE USE OF VACCINATION AS AN EFFORT TO PREVENT THE SPREAD OF THE COVID-19 VIRUS IN THE PERSPECTIVE OF ISLAMIC LAW - Harisman, Harisman (Proceeding International Seminar of Islamic Studies, 2023)
This article intends to analyze the use of vaccination as an effort to prevent the spread of the covid 19 virus from the perspective of Islamic law. Because in the midst of the community there are still many doubts about vaccination. For this reason, normative research was carried out with study materials originating from the Qur'an, hadith and various literature related to this discussion. The results were analyzed qualitatively which were then described. It can be found that the use of vaccination in preventing the Covid-19 virus is justified as long as it fulfills sharia provisions based on considerations, namely: 1) an emergency situation (daruriyah) by providing relief (rukhsah) with the intention of eliminating mafsadad, and 2) benefit (maslaha mursalah) by attention to three aspects, namely: its influence, its scope, and the strength of its argument.